Characteristics of waterproof failure and optimal width of narrow coal pillars under the coupled effects of mining, excavation and seepage - Dingchao Chen; Xiangyu Wang; Jianbiao Bai; Menglong Li (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract The failure of waterproof coal pillars under the coupled effects of mining, excavation and water seepage is a significant factor contributing to sudden water inflow accidents in underground roadways. Investigating the instability characteristics and optimal width of waterproof coal pillars holds vital significance for water control and resource protection in mines. This study focus on the rational width of waterproof coal pillar at Dongzhuang Coal Mine in Shanxi Province. Using FLAC3D, a fluid–structure interaction numerical model of waterproof coal pillar was established, revealing the coupling characteristics of stress fields, plastic zones, and seepage zones within coal pillars under the influence of mining, excavation and water infiltration weakening. Furthermore, the stability characteristics of waterproof coal pillars with different widths were compared. The results are as follows: (1) Under the combined action of overlying strata pressure and water pressure from the gob, the coal mass on the water-inflow side of coal pillar is the first to fail. Additionally, with the infiltration of water, the elastic modulus, cohesion, and friction angle of the coal mass in the seepage zone decrease. (2) The lifecycle of waterproof coal pillar can be divided into three stages: working face mining, water infiltration from the gob, and roadway excavation. Based on this, the connectivity between plastic zones and seepage zones serves as the critical condition for the stability of waterproof coal pillar was proposed. (3) When the width of waterproof coal pillar is 3 m and 5 m, plastic zones become connected, forming a water-conducting channel. When the width of waterproof coal pillar is 7 m, 9 m, and 11 m, seepage zones and plastic zones are not connected, and the coal pillar exhibits load-bearing and water-barrier properties.